Pendidikan Karakter Bangsa dalam Perspektif Perubahan Global - Huda, Syamsul (Media Akademika, 2012)
In the listening problems of human resource development in the XXI century, identified four forces in the era of globalization, the international and regional cooperation, the process of democratization and human rights, the rapid development of science and technology, and national identity. The four global forces define the vision, mission, and programs for the development of education and training in Indonesia. Global forces constitute a major force to reckon with in the developing human resources in Indonesia as a nation-state (nation-state) that diversity has a special problem in the face of the wave of globalization. In the era of globalization, one issue that stands out is the position of nation-state (nation-state). Huntington is alarming erosion of the role of the nation-state in the era of globalization. According to Huntington State and Nation fundamentally different. Nation is an ethnic and cultural communities. This is what is the source of the nationâs identity. The state is a political institution. And this is a source of power.